A cross sectional study to assess the diagnostic and management practices of general practitioners regarding tuberculosis in an urban slum of Mumbai, Maharashtra - Sawase, G. B.; Achrya, S. M.; Shinde, R. R. (International Journal Of Community Medicine And Public Health, 2017)
Background: India has large and growing private medical sector and it is observed that Private Practitioners are generally the first point of contact for significant proportion of patients with tuberculosis. Hence the present study was carried out to assess the diagnostic and management practices for tuberculosis among the private practitioners in an urban slum area. Methods: A cross sectional study was conducted in the field practice area of Urban Health Centre attached to the teaching hospital and medical college. A total of 76 Private Practitioners practising in the field practice area were contacted, explained the purpose and benefits of the study, 67 private practitioners gave consent for involvement in the study. A semi structured and pretested questionnaire was used to interview the private practitioners. Data was analyzed by using SPSS software version 17.0. Results: Among 67 Private Practitioners in the area only 19 (28.4%) doctors mentioned that they diagnose TB patients in their clinic and start the diagnosed TB patients on treatment. Persistent cough (97%), fever (86.5%), weight loss (58.2%) were the most common symptoms of TB identified by these doctors. The mean duration for suspecting TB mentioned was 3.79 weeks. Chest x-ray was the most common (85.1%) investigation advised. HRZE was the drug regimen of choice whereas few doctors gave various anti-TB drugs including 2nd line drugs like kanamycin, PAS, cycloserine to their patients. Conclusions: In present study showed majority of the private practitioners are neither updated nor very particular about the diagnosis and correct regimen of anti TB therapy. A few doctors also used 2nd line anti-TB drugs drugs like kanamycin, PAS, cycloserine to their patients which shows the likely irrational use of the few available anti-tuberculosis drugs, which may favour the emergence and spread of drug resistance.